A Ceramic‐Based Separator for High‐Temperature Supercapacitors. Issue 2 (4th December 2017) - Qin, Bin; Han, Yu; Ren, Yuxin; Sui, Dong; Zhou, Ying; Zhang, Miao; Sun, Zhenhe; Ma, Yanfeng; Chen, Yongsheng
Abstract: Currently, supercapacitors have the shortcoming of limited operation temperature mainly owing to the low thermal stability of separators, which seriously hinder their application at high temperatures. In this work, a simple and universal method for the fabrication of high‐temperature standing ceramic‐based separators is reported. It was demonstrated that such a separator can withstand over 350 °C without any shrinkage. Supercapacitors fabricated by using such separators can be operated at as high as 120 °C efficiently and even after 9000 cycles at 2.5 V operation voltage, their capacitance still retained approximately 88 % of their initial performance. To the best of our knowledge, this is the first report of a separator with such high thermal stability. Abstract : Separators for supercapacitors : Separators that can withstand temperatures higher than 350 °C and possess good tensile strength have not been reported yet. A simple and universal method for the fabrication of supercapacitor separators that can withstand over 350 °C without any shrinkage has been developed. Supercapacitors fabricated by using such a separator can be operated at 120 °C efficiently with remarkable capacitance retention.